TINJAUAN EKONOMI SYARIAH TERHADAP JUAL BELI PUPUK DOLOMIT SECARA TANGGUH: Studi Kasus Di Desa Wadeng Kecamatan Sidayu Kabupaten Gresik - Eriel Azimi; Moh. Ya'kub Ya'kub; Muhammad Shaiful Umam Shaiful (SEKOLAH TINGGI ILMU SYARIAH ABU ZAIRI BONDOWOSO, 2025)
In society, buying and selling practices are often carried out without proper understanding of their compliance with sharia principles. One example is the deferred payment sale (jual beli secara tangguh) of dolomite fertilizer in Wadeng Village, Sidayu Sub-district, Gresik Regency, which has emerged as a solution to farmers’ limited capital. However, this practice raises several concerns from a sharia perspective, such as price markup, unclear contract terms, and the potential elements of riba and gharar. This study aims to examine the conformity of such practices with the principles of Islamic economics. The research adopts a qualitative approach using a case study method through observation, interviews, and documentation. The findings indicate that although the deferred system offers convenience to farmers, there are deviations from sharia principles, particularly in price transparency, clarity of payment deadlines, and the absence of written contracts. Therefore, there is a need for better understanding and education regarding sharia contracts, particularly bai’ muajjal, to ensure that transactions are conducted fairly and in accordance with Islamic guidelines. Keywords: Islamic Economics, Buying and Selling, Dolomite Fertilizer, Deferred System, Bai’ Muajjal